How common are palliative care needs among older people who die in the emergency department?. Issue 2 (1st September 2011) - Beynon, Teresa; Gomes, Barbara; Murtagh, Fliss E M; Glucksman, Ed; Parfitt, Andy; Burman, Rachel; Edmonds, Polly; Carey, Irene; Keep, Jeff; Higginson, Irene J
Abstract : Objective: To determine the prevalence and nature of palliative care needs in people aged 65 years or more (65+) who die in emergency departments (EDs). Methods: This was a retrospective analysis of routine hospital data from two EDs in South London. Patients aged 65+ living in the hospitals' catchment area who died in the ED during a 1 year period (2006–2007) were included. Palliative care needs identified by diagnosis and symptoms, and problems likely to benefit from palliative care documented in clinical records 3 months prior to the final ED attendance were extracted. Results: Over 1 year, 102 people aged 65+ died in the ED, frequently following an acute event (n=90). 63.7% presented out of hours. 98/102 were admitted by ambulance, over half (n=59) from home. Half (n=50) had attended the same ED or been admitted to the same hospital in the previous 12 months. Over half (58/102) presented with diagnoses that signalled palliative care need. Of these, 29 had recorded symptoms a week before death and 28 had complex social issues 3 months prior to death. Only eight were known to palliative care services. Conclusions: There is considerable palliative care need among older people who ultimately died in the ED, of whom only a minority were known to palliative care services in this study. Previous ED and hospital admission suggest opportunities for referral and forward planning. More older people in need of palliative care must be identified and managed earlier to avoid future undesired admissions and deaths in hospital.